Pengalaman dan Pelatihan untuk Meningkatkan Kesiapsiagaan Bencana Perawat Unit Gawat Darurat - Herlin Lidya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Disaster conditions have a major impact on health services. A large spike in patients in a short time can cause nurses to be overwhelmed in treating patients, especially disaster victims. Therefore, emergency room nurses as the first line of defense need to have good disaster preparedness, especially triage and appropriate treatment for patients. This study aimed to describe the factors that influence the disaster preparedness of emergency nurses in providing disaster management. This study was a literature review. The electronic databases used in the literature search consisted of ProQuest, ScienceDirect, SAGE Knowledge and Emerald Insight with the keywords "disaster", "preparedness", "emergency", "nurse"; and using the Boolean operator "AND". The criteria used in the literature search included articles published in the last 5 years, in English or Indonesian. During the study, 436 articles were obtained and after screening, 7 articles were found that matched the study objectives. Based on the results of the study, it was found that the factors that influence disaster preparedness in emergency nurses are experience as an emergency response team, disaster preparedness training and education. It was concluded that disaster preparedness training and education on an ongoing basis needs to be carried out to increase the knowledge and disaster preparedness of emergency nurses.Keywords: disaster; preparedness; emergency nurse; training ABSTRAK Kondisi bencana memberikan dampak besar pada pelayanan kesehatan. Lonjakan pasien yang besar dalam waktu singkat dapat menyebabkan perawat kewalahan dalam menangani pasien, khususnya korban bencana. Oleh karena itu perawat unit gawat darurat sebagai garda pertama perlu memiliki kesiapsiagaan bencana yang baik, khsususnya triase dan penanganan yang tepat bagi pasien. Studi ini bertujuan untuk menggambarkan faktor yang mempengaruhi kesiapsiagaan bencana para perawat gawat darurat dalam memberikan penanganan kebencanaan. Studi ini merupakan tinjauan literatur. Database elektronik yang digunakan dalam pencarian literatur terdiri dari ProQuest, ScienceDirect, SAGE Knowledge dan Emerald Insight dengan kata kunci “disaster”, “preparedness”, “emergency”, “nurse”; serta menggunakan operator Boolean “AND”. Kriteria yang digunakan dalam pencarian literatur di antaranya adalah artikel terbitan 5 tahun terakhir, dalam bahasa Inggris atau Bahasa Indonesia. Selama studi didapatkan 436 artikel dan setelah dilakukan screening didapatkan artikel yang sesuai dengan tujuan studi berjumlah 7 artikel. Berdasarkan hasil telaah didapatkan faktor yang mempengaruhi kesiapsiagaan bencana pada perawat gawat darurat yaitu pengalaman menjadi tim tanggap darurat, pelatihan kesiapsiagaan bencana dan pendidikan. Disimpulkan bahwa pelatihan dan pendidikan kesiapsiagaan bencana secara berkesinambungan perlu dilakukan untuk meningkatkan pengetahuan dan kesiapsiagaan bencana perawat gawat darurat.Kata kunci: bencana; kesiapsiagaan;  perawat gawat darurat; pelatihan